25-{27:[(36-27:3)+42:7×3}
Răspunsuri la întrebare
Răspuns de
4
25-{27:[36-9)+6x3}=
25-[27:(27+18)]=
25-(27:45)=
25-0,6=
24,4
25-[27:(27+18)]=
25-(27:45)=
25-0,6=
24,4
Răspuns de
4
25-{27:[(36-9)+6×3}
25-[27:(27+6×3)]
25-[27:(27+18)]
25-(27:45)
25-0,6
=24,4
25-[27:(27+6×3)]
25-[27:(27+18)]
25-(27:45)
25-0,6
=24,4
Alte întrebări interesante
Biologie,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă